2014
DOI: 10.1093/jac/dku209
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the chikungunya virus non-structural proteins cause resistance to favipiravir (T-705), a broad-spectrum antiviral

Abstract: This study provides an important insight into the precise molecular mechanism by which favipiravir exerts its antiviral activity against (alpha)viruses, which may be of help in designing other potent broad-spectrum antivirals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
196
2
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(207 citation statements)
references
References 45 publications
6
196
2
3
Order By: Relevance
“…Our data indicate that T-705 does not induce lethal mutagenesis on HMPV genomes but does have a direct effect on the HMPV polymerase. This is in line with the activity against the influenza virus RNA-dependent RNA polymerase reported by Kiso et al (50) and with data reported for the chikungunya virus, in which a single mutation in the polymerase protein was sufficient to make the virus resistant to treatment (47). Although it is possible that T-705 interferes with viral morphogenesis at a late stage of the infectious cycle, T-705 is a nucleotide analog, and its mechanism of action is thought to be related to the selective inhibition of viral RNA-dependent RNA polymerases of influenza virus and many other RNA viruses (21,23 (32,51).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our data indicate that T-705 does not induce lethal mutagenesis on HMPV genomes but does have a direct effect on the HMPV polymerase. This is in line with the activity against the influenza virus RNA-dependent RNA polymerase reported by Kiso et al (50) and with data reported for the chikungunya virus, in which a single mutation in the polymerase protein was sufficient to make the virus resistant to treatment (47). Although it is possible that T-705 interferes with viral morphogenesis at a late stage of the infectious cycle, T-705 is a nucleotide analog, and its mechanism of action is thought to be related to the selective inhibition of viral RNA-dependent RNA polymerases of influenza virus and many other RNA viruses (21,23 (32,51).…”
Section: Discussionsupporting
confidence: 90%
“…Both direct inhibition of the polymerase and induction of lethal mutagenesis have been described (23,24,47,49). In the T-705-treated hamsters inoculated with HMPV, viral genomes were detected in all animals even when the animals were treated at high doses.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Taken together, the in vivo results show dual roles of berberine as an antiviral and an anti-inflammatory agent, and this is one of the few reports of an antiviral against CHIKV showing efficacy in a mouse model (3). Earlier, favipiravir was shown to protect against neurological complications and death in a mouse model of lethal CHIKV infection, which does not represent disease outcomes in the majority of CHIKV-infected patients (65). Interestingly, treatments were given either 24 h before infection or 4 h p.i., whereas in our study, berberine treatment was started only at 1 dpi.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have identified small-molecule inhibitors that inhibit CHIKV replication in cell culture (9)(10)(11)(12)(13)(14). Some nucleoside analogs, such as ribavirin, have also been shown to interfere with CHIKV replication.…”
mentioning
confidence: 99%